2018
DOI: 10.3390/cancers10110422
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Hippo Pathway for Breast Cancer Therapy

Abstract: Breast cancer (BC) is one of the most prominent diseases in the world, and the treatments for BC have many limitations, such as resistance and a lack of reliable biomarkers. Currently the Hippo pathway is emerging as a tumor suppressor pathway with its four core components that regulate downstream transcriptional targets. In this review, we introduce the present targeted therapies of BC, and then discuss the roles of the Hippo pathway in BC. Finally, we summarize the evidence of the small molecule inhibitors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 139 publications
0
76
0
Order By: Relevance
“…In fact, our study identified for the first time CYLD as a negative regulator of the YAP/TAZ transcriptional regulators in confluent culture conditions. Hyperactivation of the YAP/TAZ complex has previously been involved in the progression of breast cancer by promoting migration and invasion [51]. Our analysis indicates that one of the molecular alterations that can induce the activity of these transcription factors in mammary epithelial cells is the downregulation of CYLD.…”
Section: Discussionmentioning
confidence: 53%
“…In fact, our study identified for the first time CYLD as a negative regulator of the YAP/TAZ transcriptional regulators in confluent culture conditions. Hyperactivation of the YAP/TAZ complex has previously been involved in the progression of breast cancer by promoting migration and invasion [51]. Our analysis indicates that one of the molecular alterations that can induce the activity of these transcription factors in mammary epithelial cells is the downregulation of CYLD.…”
Section: Discussionmentioning
confidence: 53%
“…The Hippo pathway plays important roles in tumor suppression and immune response. However, alterations in this pathway are involved in the BC tumorigenesis and metastasis 85 . Lastly, the thyroid hormone pathway plays an important role as regulator of growth and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo pathway plays important roles in immune response, stem cell function and tumor suppression. However, alterations in this pathway are involved in the BC tumorigenesis and metastasis 79 . Lastly, the thyroid hormone signaling pathway is an important regulator of growth and metabolism.…”
Section: Discussionmentioning
confidence: 99%